Chelating and antioxidant properties of l-Dopa containing tetrapeptide for the treatment of neurodegenerative diseases. (October 2018) - Cacciatore, Ivana; Marinelli, Lisa; Di Stefano, Antonio; Di Marco, Valerio; Orlando, Giustino; Gabriele, Mirko; Gatta, Daniela Maria Pia; Ferrone, Alessio; Franceschelli, Sara; Speranza, Lorenza; Patruno, Antonia
Abstract: Neurodegenerative diseases share a common pathogenetic mechanism involving aggregation and deposition of misfolded proteins, oxidative stress, metal dyshomeostasis, and glutamate exicitotoxicity, which lead to progressive dysfunction of central nervous system (CNS). A potential strategy to counteract these deleterious events at neuronal level is represented by the employment of a novel class of multi-target therapeutic agents that selectively and simultaneously hit these targets In this paper, we report the metal binding and antioxidant properties of a novel metal-protein attenuating peptide, GSH-LD, a tetrapeptide obtained by linking glutathione, a well-known antioxidant tripeptide, to L-Dopa. Results demonstrated that GSH-LD possesses chelating capabilities in order to selectively target the excess of metals without interfere with metal-containing antioxidant enzymes. Moreover, antioxidant assays revealed a large contribution of GSH-LD to restore the antioxidant defences of damaged neuronal cells Graphical abstract: Highlights: GSH-LD as potential tool to treat neurodegenerative disorders GSH-LD as chelating agent of metals GSH-LD may reduce oxidative stress in neurodegenerative diseases